Fatigue Is Common in Immunoglobulin G Subclass Deficiency and Correlates With Inflammatory Response and Need for Immunoglobulin Replacement Therapy - Wågström, Per; Nilsdotter-Augustinsson, Åsa; Nilsson, Mats; Björkander, Janne; Dahle, Charlotte; Nyström, Sofia (Frontiers in Immunology, 2022)
Purpose: Individuals with immunoglobulin G deficiency (IgGsd) often complain of fatigue. The correlation between systemic inflammation and fatigue is unknown. In this study perceived quality of life (QoL) and fatigue in individuals with IgGsd, on and off immunoglobulin replacement therapy (IgRT) were correlated to inflammatory markers in plasma to identify the subgroup that benefits from IgRT. Method: Thirty-five IgGsd-patients were sampled on three occasions: at baseline, after being on IgRT for at least 18 months, and 18 months after discontinuation of IgRT. Short form 36, EQ-5D-5L visual analogue scale and fatigue impact scale questionnaires were used for evaluation of QoL and fatigue. Furthermore, a panel of 92 inflammatory markers were analysed in plasma. Thirty-two gender- and age-matched healthy individuals were included as controls and sampled on one occasion. Results: QoL was lower and perceived fatigue higher in IgGsd compared to the controls. Severe fatigue and low QoL were associated with the need to restart IgRT (which is considered in IgGsd-individuals with a high burden of infections in Sweden). Twenty-five inflammatory factors were dysregulated in IgGsd and the plasma protein patterns were similar regardless of whether IgRT was ongoing or not. Enrichment analysis indicated IL-10 signalling as the most affected pathway. Severe fatigue was associated with decreased levels of the neurotrophic factors VEGFA and CSF-1. Conclusion: Fatigue is a major contributory factor to impaired health-related QoL in IgGsd and is related to the need for IgRT. Low grade systemic inflammation is a potential driver of fatigue. In addition to the burden of infections, we suggest the degree of fatigue should be considered when the decision to introduce IgRT is made.